entropy_variants0.6 - Underwood, Zachary E.; Mandeville, Elizabeth G.; Walters, Annika W. (Dryad Digital Repository, 2015)
Input file for analysis with the "entropy" model. This file is a filtered version of the VCF file, including genotype likelihoods for loci with MAF>1%. Additionally, we randomly selected 1 SNP per contig for contigs with multiple variant sites, to ensure independence of SNPs.